PENGEMBANGAN ALAT PERAGA FISIKA PADA MATERI VISKOSITAS SEBAGAI MEDIA PEMBELAJARAN - Sumirat Dyah Wulandari; Undang Rosidin; Abdurrahman - (Jurnal Pembelajaran Fisika, 2013)
Learning media is something which very important in the learning process because it will become one of the critical success factors of learning. Utilization of learning media, especially visual aids of physics are necessary for effective in learning activities. Therefore, there has been developed a visual aid of viscosity with different designs to make more variety of learning media which already exists. The purpose of the research is make a visual aids of physics in viscosity and its worksheet (LKS). The procedure including needs analysis, formulate the purpose of the learning, formulate a part of subject matter, preparing manuscripts media, the first model, expert validation, field trials, and the final product. Validation is performed by physicists and physics teachers. The results of the validation explain that visual aid of viscosity and its worksheet has been accordance with the planned design and deserves to be used as a learning media. The field trials was at SMA Muhammadiyah 2 Bandar Lampung twice, that is one-on-one test with 4 students and small groups test with 20 students of 2nd grade Science class. The results were the visual aids and its worksheet is very useful for learning. Besides, the design of the visual aids is very attractive, easy to use, and the materials are relatively inexpensive.Keywords: aids, media, research development, and viscosity.